2004
DOI: 10.1210/en.2004-0407
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Rat Ovarian Gene Expression Database

Abstract: The pituitary gonadotropins play a key role in follicular development and ovulation through the induction of specific genes. To identify these genes, we have constructed a genome-wide rat ovarian gene expression database (rOGED). The database was constructed from total RNA isolated from intact ovaries, granulosa cells, or residual ovarian tissues collected from immature pregnant mare serum gonadotropin (PMSG)/human chorionic gonadotropin-treated rats at 0 h (no PMSG), 12 h, and 48 h post PMSG, as well as 6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 73 publications
10
78
0
Order By: Relevance
“…Most studies have not explicitly quantified A2M expression in crustacean ovary, although one study reports weak expression in ovary of kuruma shrimp [52]. A2M expression has been more thoroughly studied in mammalian ovaries, where it regulates protease activity necessary for ovulation and associated tissue remodeling [53,54]. Other studies of A2M expression in crustacean tissues have found that A2M transcripts are expressed most strongly in hemocytes [52,55,56] and that expression can be induced by microbial challenge [52,55,57].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have not explicitly quantified A2M expression in crustacean ovary, although one study reports weak expression in ovary of kuruma shrimp [52]. A2M expression has been more thoroughly studied in mammalian ovaries, where it regulates protease activity necessary for ovulation and associated tissue remodeling [53,54]. Other studies of A2M expression in crustacean tissues have found that A2M transcripts are expressed most strongly in hemocytes [52,55,56] and that expression can be induced by microbial challenge [52,55,57].…”
Section: Discussionmentioning
confidence: 99%
“…mRNA expression of several complement components, including C1qb, C3, C4, C5r1, factor h, and C1 qbp, in the ovary of the superovulated immature rat (Jo et al 2004) (http://web5.mccs.uky.edu/kolab/rogedendo.aspx). Thus, it is clear that many immune factors, including complement, are expressed in the periovulatory ovary, strongly indicating that the expression of GPI-DAF Figure 5 GPI-DAF mRNA expression is not directly controlled by P4 or PG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…aspx), which was previously developed in our laboratory. The procedures used are described in detail elsewhere (Jo et al 2004). The database provides the gene expression profiles of all genes and expressed sequence tags included in the Affymetrix Rat Expression 230A and 230B GeneChips.…”
Section: Rogedmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive in situ hybridization analyses for brain sections were performed using genes expressed in the brain, and the results are available from the database (http://www.genepaint.org) (8). Cellular localization of genes was determined using a GFP-fused reporter system (9,10).…”
Section: Introductionmentioning
confidence: 99%